The Analysis of the Popularity of Renewable Energy Vehicle Usage in European Countries - Madiyoh, Abdulhakim; Samor, Anas (Al-HIKMAH Journal, 2024)
This research article aims to: 1) analyze the popularity of various types of engine vehicles in European countries, and 2) evaluate and rank the popularity of renewable energy vehicle usage among European member countries. The population used was secondary panel data collected from historical statistics on new vehicle registrations between July 2021 and June 2023, covering a total of 24 months from 31 European countries. The analysis utilizes market share statistics, growth rates, Paired simple t-test, and the TOPSIS technique. The statistical analysis of vehicle registrations in each European country from 2021 to 2023 found that the average number of vehicles registered across Europe was 965,409 vehicles per month. Germany had the highest number of vehicle registrations, accounting for 22.79%, followed by the United Kingdom (14.25%) and France (13.62%). The analysis of engine type popularity revealed that new gasoline-engine vehicles had the highest market share at 37.34% of all vehicles but showed a growth rate of -10.78%. HEVs came next with a market share of 21.81% and a growth rate of 1.63%. BEVs had a market share of 17.85% with a growth rate of 48.51%. Diesel engines held a market share of 12.75% with a growth rate of -16.01%, and PHEVs had a market share of 8.52% with a growth rate of 17.03%. The Paired Simple t-test found that the popularity of gasoline and diesel-powered vehicles decreased, while the popularity of electric vehicles increased significantly at the 0.05 statistical level.The TOPSIS technique was used to evaluate the ranking of European countries that excel in adopting renewable energy vehicles in 2023. The results showed that Norway had the highest Closeness Coefficient at 0.6581825, followed by Ireland (0.4717417), Finland (0.4692445), and Sweden (0.4633604), respectively.